Solvothermal synthesis of Fe doped MnSnO3: An approach of wide bandgap perovskite towards optical, luminescence, and electrochemical properties. (5th August 2021) - Bhat, Aadil Ahmad; Assadullah, Insaaf; Malik, Javied Hamid; Sharma, Arti; Tomar, Radha
Summary: The present article investigates the fabrication of MnSnO3, and Fe doped MnSnO3 perovskite. We are reporting for the first time Fe doping perovskite material. The synthesis has been carried out under subcritical conditions. The optical, electrochemical, and luminescence properties were investigated. The structural determination of nanostructures has been carried out through XRD and Fourier transform infrared (FTIR). Furthermore, scanning electron microscope (SEM) technique was applied to figure out the morphology of nanostructured materials. Later on, the investigation of luminescent properties of Fe doped MnSnO3 material has been carried out by photo luminance. In addition, the material shows applicability toward photoluminescence properties. Commission Internationale de l'Éclairage (CIE) co‐ordinate is used to see the illumination of these materials. Insufficient to this, the optical absorption concludes the reduction of band gap values and tunes up to 2.6 eV from 3.1 eV and makes these materials active in the visible region. Finally, the electrochemical activity reflects the pseudo capacitor behavior of synthesized material and the value of capacitance enhances with an increase in the content of iron (Fe) in the host lattice.